2000
DOI: 10.1099/0022-1317-81-3-759
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of a hepatitis C virus RNA-dependent RNA polymerase mutant lacking the C-terminal hydrophobic sequence

Abstract: The RNA-dependent RNA polymerase activity of hepatitis C virus is carried out by the NS5B protein.The full-length protein was previously purified as a non-fusion protein from insect cells infected with a recombinant baculovirus. The characterization is now described of a C-terminal hydrophobic domain deletion mutant of NS5B purified from E. coli. In addition to increased solubility, deletion of this sequence also positively affected the polymerase enzymatic activity. The efficiency of nucleotide polymerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 25 publications
5
82
0
Order By: Relevance
“…Expression, Purification, and Intrinsic Fluorescence Properties of HCV NS5B Protein-The HCV NS5B protein contains motifs shared by RNA polymerases, and its activity has been shown to be dependent on the presence of either magnesium or manganese ions (8,14,(22)(23)(24)(25)(26). To further characterize the metal binding activity of the enzyme, the NS5B protein was expressed in E. coli as described under "Experimental Procedures."…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression, Purification, and Intrinsic Fluorescence Properties of HCV NS5B Protein-The HCV NS5B protein contains motifs shared by RNA polymerases, and its activity has been shown to be dependent on the presence of either magnesium or manganese ions (8,14,(22)(23)(24)(25)(26). To further characterize the metal binding activity of the enzyme, the NS5B protein was expressed in E. coli as described under "Experimental Procedures."…”
Section: Resultsmentioning
confidence: 99%
“…To further characterize the metal binding activity of the enzyme, the NS5B protein was expressed in E. coli as described under "Experimental Procedures." A truncated form of NS5B (NS5B⌬21) lacking the previously identified 21-amino acid hydrophobic domain (14,22,24,25) was expressed and purified. SDS-PAGE analysis showed that the 65-kDa NS5B⌬21 protein was the predominant polypeptide in the purified fraction (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological activity of the compounds against NS5B polymerase were evaluated in a reaction buffer containing 20 mM TriseHCl (pH 7.0), 100 mM NaCl, 100 mM sodium glutamate, 0.1 mM DTT, 0.01% BSA, 0.01% Tween-20, 5% glycerol, 20 U/mL of RNase Out, 0.25 mM of polyrA/U12, 25 mM UTP, 2 mCi [alpha-32 P]UTP, 300 ng of NS5BCD21and 1.0 mM MnCl2 with or without inhibitors (100 mM) in a total volume of 25 mL for 1 h at 30 C as previously described [26,27]. Reactions were terminated by the addition of ice-cold 5% (v/v) trichloroacetic acid (TCA) containing 0.5 mM pyrophosphate.…”
Section: Ns5b Inhibition Assaymentioning
confidence: 99%
“…Another TNTase-free HCV NS5B with deletion of the 21 C-terminal hydrophobic amino acids copied HCV X-RNA inefficiently by internal initiation (Kashiwagi et al, 2002). Tomei et al reported that the full-length NS5B has a slightly enhanced processivity compared to the truncated form of NS5B (Tomei et al, 2000). Since all the HCV NS5B proteins used for structure determination were missing these hydrophobic residues (Bressanelli et al, 1999;Lesburg et al, 1999;Butcher et al, 2001), knowledge of the topological characteristics of the C-terminal hydrophobic domain of NS5B is still needed to understand the role of this region in enzymatic function of NS5B.…”
Section: Introductionmentioning
confidence: 99%